Energy of Unmanned Aerial Vehicle (UAV) Windmill (theory, streamlined airflow) - L. I. Grechikhin; D. A. Saharuk; A. B. Sivashko; A. A. Tsanava (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
A windmill theory as an open power system is resolved in the paper. The paper presents a mechanism of a frontal resistance and a thrust load of the operating windmill which is based on occurrence of an active environmental component and formulates the conditions under which any minimum resistance and maximum thrust load are realized. An algorithm and software for calculation of windmill streamlining pattern are developed in the paper. The calculation results are given the paper.